Metacognition researches in Turkey, Japan and Singapore - Ayşe Elitok Kesici; Derya Güvercin; Hızır Küçükakça (Institute of Advanced Engineering and Science, 2021)
In this study, fundamental researches on “metacognition” in Turkey, Japan and Singapore between the years of 2010 and 2020 were examined and conclusions were made in terms of comparative education. For this purpose, the data of the research was collected by document scanning method and the data were analyzed using the document review technique, which is one of the qualitative research method techniques. Years of studies, countries, objectives, research methods, sample working group, data analysis methods and results; it has been examined according to comparative education approaches and data collection techniques. As a result, quantitative research methods are seen to be frequently used in researches on metacognition in these three countries. It has been determined that experimental studies are the main research patterns of the metacognition studies conducted in three countries. Metacognitive awareness scales are the most used data collection tools in all three countries. Considered in general; the research made about metacognition in Singapore Turkey and Japan shows that the studies investigating the relationship between students' problem-solving skills and metacognition are in majority. Researches examining the relationship between metacognition and foreign language teaching are also widely discussed.